A importância do exame de mamografia na detecção precoce do câncer de mama - CIPRIANO, Carla Dayanne Cardoso (Instituto Federal do Amapá, 2021)
Mammography is an exam of great importance in screening for breast cancer. These are strategies for early detection of breast cancer, screening and early diagnosis. This study aimed to demonstrate the importance of diagnosis through mammography. The present study was based on descriptive, bibliographic research, with a quantitative approach, which investigated the importance of performing the mammography exam, the number of mammography exams performed in the cities of Amapá, and the diagnostic and screening exams registered in the Macapá from 2019 to 2020. Data analysis consisted of women and men in the following age groups: 40 to 44 years, 45 to 49 years, 50 to 54 years, 55 to 59 years, 60 to 64 years, and 65 to 69 years. The results showed the low demand for the mammography exam, especially at older ages and in the municipalities, in the capital Macapá the rate of access to the exam was higher. As for the diagnostic mammography exam, the highest index occurred in the age group between 45 and 49 years and the lowest was between 65 and 69 years, in the screening mammography the performance of the exam was prevalent between 40 and 44 years and lower among the group of patients aged 65 to 69 years. Thus, it is hoped that this study can collaborate for a differentiated service to this population, through the creation of strategies for the prevention and diagnosis of breast cancer, to reduce the costs with specific treatments.